Short Multiwall Carbon Nanotubes Promote Neuronal Differentiation of PC12 Cells via Up‐Regulation of the Neurotrophin Signaling Pathway. Issue 9 (7th November 2012) - Meng, Li; Chen, Rui; Jiang, Aihua; Wang, Liming; Wang, Peng; Li, Chen‐zhong; Bai, Ru; Zhao, Yuliang; Autrup, Herman; Chen, Chunying
Abstract Numerous unique properties of carbon nanotubes make them attractive for applications in neurobiology such as drug delivery, tissue regeneration, and as scaffolds for neuronal growth. In this study, the critical roles of the length of multiwall carbon nanotubes (MWCNTs) on a neuronal‐like model cell line PC12 cells are investiaged. Incubation of PC12 cells with carboxylated MWCNTs did not significantly affect cellular morphology and viability at lower concentrations. Short MWCNTs show higher cellular uptake and more obvious removal compared to longer ones, which can result in higher ability to promote PC12 cell differentiation. Pre‐incubation of short MWCNTs can up‐regulate the expression of neurotrophin signaling pathway‐associated TrkA/p75 receptors and Pincher/Gap43/TH proteins, which might be the underlying mechanism for the improved differentiation in PC12 cells. The current results provide insight for future applications of MWCNTs in neuron drug delivery and neurodegenerative disease treatment.